Measurement of the W boson polarisation in t¯t events from pp collisions at √s = 8 TeV in the lepton + jets channel with ATLAS - Alconada Verzini, María Josefina (2017)
This paper presents a measurement of the polarisation of W bosons from t¯t decays, reconstructed in events with one high-pT lepton and at least four jets. Data from pp collisions at the LHC were collected at √s = 8 TeV and correspond to an integrated luminosity of 20.2 fb−1. The angle θ* between the b-quark from the top quark decay and a direct W boson decay product in the W boson rest frame is sensitive to the W boson polarisation. Two different W decay products are used as polarisation analysers: the charged lepton and the down-type quark for the leptonically and hadronically decaying W boson, respectively. The most precise measurement of the W boson polarisation via the distribution of cos θ* is obtained using the leptonic analyser and events in which at least two of the jets are tagged as b-quark jets. The fitted fractions of longitudinal, left- and right-handed polarisation states are F0 = 0.709 ± 0.019, FL = 0.299 ± 0.015 and FR = −0.008 ± 0.014, and are the most precisely measured W boson polarisation fractions to date. Limits on anomalous couplings of the W tb vertex are set.